Skema Inovatif: Transformasi Digital Badan Usaha Milik Desa dalam Pemasaran Berbasis Elektronik - Esa Septian (Research and Development Agency Ministry of Home Affairs, 2021)
The existence of the Binangun Jati Unggul Village-Owned Enterprise (VOE) as an effort to improve the community’s economy and become a contributor to Village Original Income. This research aims to see problems in the management of VOE, especially in terms of marketing is still low; the author provides alternative ideas to solving the problem. The involvement of technology can create an online marketing system that is useful for the successful management of VOE. The research method used in this research is descriptive qualitative research. The results of this study are Binangun Jati Unggul VOE has not run optimally. Binangun Jati Unggul VOE is still facing problems related to the quality of human resources minimal, limited capital, and weak marketing. Development style VOE based on digital marketing as an effort to boost marketing The VOE became wider. The presence of advanced technology is a demand of the times that must be met in carrying out agricultural business activities through collaboration and synergy between agricultural economic institutions in serving the farmer’s needs. The application of digital marketing through the innovative farmer market electronic scheme (e-Pasti) is expected to provide solutions to weak marketing systems. Therefore, all agricultural activities run more effectively and efficiently, and the market share is becoming wider, which has a positive impact on the government, farmers, youth, and local communities.